DAMPAK PINJAMAN SARANA PRODUKSI TERNAK TERHADAP KESEJAHTERAAN RUMAHTANGGA PETERNAK SAPI PERAH DI LEMBANG - Juniar Atmakusuma; Bonar Marulitua Sinaga; Nunung Kusnadi; I Ketut Kariyasa (Jurnal Agribisnis Indonesia, 2019)
Most of the dairy cow farmers in Indonesia are members of the dairy cooperative who receive loan facilities for dairy cattle production and feed concentrates to be useful for increasing the productivity of dairy cows and milk as well as to increase national milk production. The purpose of this study was to identify the business of dairy farmers, and analyze the impact of loans for dairy cattle production facilities on production, income and household well-being of dairy farmers. The analytical method consisted of descriptive analysis and household economic model of dairy farmers in the form of simultaneous equations with sample households of 97 member farmers and 46 non-member farmers in Lembang, West Java. The results of the study show that the age of the farmer is in a productive age with a long experience of farming so that the opportunity for formal education is limited. The scale of ownership of small dairy cows with a low percentage of lactation cows resulting in low milk productivity. Ownership of dairy cattle influences the dairy cattle loan and the price of feed concentrate affects the loan of feed concentrate input.  The impact of the cooperative giving loans on dairy cows is greater than giving loans on feed concentrates on increasing the income of dairy cow business and dairy farmer’s household well-being.